FIBROGLIAL PROCOLAGENA DE LAS GLANDULAS SUDORALES DE LA AXILA - VILLASENOR CASTELLANOS, C (Universidad Nacional Autónoma, Instituto Geología, CD MEXICO, DF, MEX, 1946)
A special variety of plasmocytes exists, derived from the histo-cytes of the conjunctive tissue, which can be designated as histoid plasmocytes The following characteristics have been established: (a) larger in size in relation to lymphoid plasrno-cytes,
BOL INST ESTUD MED BIOL
Keywords: FIBROGLIAL, PRECOLAGENA, GLÁNDULAS, SUDORALES, AXILA; CIENCIAS MEDICAS; MEDICINA INTERNA; ENDOCRINOLOGIA